Penerapan Posisi Passive Leg Raising Dalam Peningkatan Tekanan Darah Pada Pasien Syok Sepsis Di IGD - Salimah Rahma; Fitri Arofiati (PPNI UNIMMAN, 2024)
Background: Sepsis is characterized by the body's excessive inflammatory response to infection, potentially leading to life-threatening organ dysfunction. Additionally, sepsis can induce hypotension involving both pro-inflammatory and anti-inflammatory body responses. One non-pharmacological intervention for hypotension is Passive Leg Raising (PLR), where the patient lies flat while the legs are raised at a 45-degree angle. Objective: To determinethe effect of increasing blood pressure in septic shock patients after PLR therapy. Methods: A case study conducted on May 12, 2024, at the Emergency Room of PKU Muhammadiyah Yogyakarta, observed patients blood pressure and mean arterial pressure (MAP) every 30 minutes over 1 hour using bedside monitoring before and 30 minutes after vasopressor administration. Results: PLR for 60 minutes increased systolic blood pressure by 8mmHg, diastolic by 7mmHg, and MAP by 8mmHg. Subsequent vasopressor addition for 30 minutes yielded more significant increases: systolic blood pressure rose by 35mmHg, diastolic by 26mmHg, and MAP by 37mmHg. Conclusion: PLR administration increases blood pressure, but combining it with vasopressors proves more effective in septic shock management.